Egyptian National Postal Organization : Postal Financial Services and Access to Finance - World Bank (World Bank, Washington, DC, 2014)
ENPO is an organization employing 48,000 staff and operating a network of more than 9,000 access points (of which 3,500 post offices, 6,500 agencies, of which 1,500 are currently active). A commercial entity with management autonomy, ENPO is primarily a provider of basic financial services. Other services are mail (regular and express), parcels and Government services. Postal financial services, with three main business lines (savings, payments and giro services) and 15 million savings accounts, generate around 50% to 60% of ENPO s total revenue, and occupy an estimated 15% of ENPO s staff. Although available accounting and financial information are limited, it seems that postal financial services are operated at a profit. For ENPO which is currently in a transition phase from an administration-type of organization, moving towards a corporate-type of organization, the strategic option will play as an accelerator of change (in case the Government decides for a drastic move towards bancarization) or as a consolidator of incremental reform (in case the Government opts for a progressive approach, potentially using alternative approach to grab the business opportunities of growth, but likely avoiding social tensions within the organization). In any case, moving forward the postal financial services agenda will call for (i) a review of the legal, regulatory and institutional set-up, (ii) building capacity in the network and assessing the return on investments, (iii) rapidly identifying the postal financial services as a business unit within the organization and assess its contribution to profit, as well as (iv) getting a better understanding of the cost structure so as to enable ENPO to be in a strong position during negotiations of service level agreement.